Keanekaragaman Mesofauna Tanah pada Lahan Pertanian Sayuran Konvensional dan Organik di Kecamatan Baturiti - Silalahi, Yohanna; Kesumadewi, Anak Agung Istri; Atmaja, I Wayan Dana (Agrotrop : Journal on Agriculture Science; Vol 13 No 3 (2023)DO - 10.24843/AJoAS.2023.v13.i03.p13, 2023)
Diversity of Soil Mesofauna on Conventional Agricultural Land and Organic in Baturiti Sub-District. A comparative descriptive research was carried out to determine the impact of conventional and organic vegetable cultivation systems on the diversity of soil mesofauna in Baturiti District. Each three replicates of soil samples were taken from 5 types of vegetable plants cultivated on conventional agricultural and organic agricultural lands. The samples were taken at a depth of 0-20 cm from purposive vegetable field. Soil mesofauna was separately extracted from each soil sample using the Barlesse-Tullgren extraction method with under 45 watt lamp for 48 hours. The morphology of the mesofauna was observed under stereo microscope. The research results show that the soil mesofauna on conventional agricultural land consists of 7 orders, 18 families, 19 genera and 22 species with a total of 31 individuals per m2, while on organic agricultural land there are 7 orders, 17 families, 20 genera and 23 species with the number of individuals was 45. The soil mesofauna dominance index in all research locations was low between 0.02-0.15. The soil mesofauna diversity index in all research locations is in the medium category, namely between 1.87-2.62. The evenness index of soil mesofauna types throughout the research location is in the high category, namely between 0.95-1.09.